Camera Raw Image Processing and Registration Using Raw CFA Images (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Abstract— RAW — a multimedia file with image details collected by the camera concerning the pixel values of the sensor and the text information. The processing of RAW is important ignoring the replication of images, to save space, to encourage the operation of image files and to have continuous capture. The RAW is emphasized as a digital adverse and varies according to the scale depending on the manufacturer of the hardware. The proposed workflow is to Extract and process RAW sensor information from the RAW files and view the picture format details. Image quality is the significant parametric quantity that defines the captured RAW image. With no built-in compression (RAW) the most extreme resolution brings about picture from any advanced camera. The MATLAB R2016a was used to execute the purpose of the workflow and the analysis. We examined direct registration of raw images based on an imaging model, which shows precise estimation of motion among severely aliased raw images. The proposed method is verified through experiments using synthetic and real images.